Exploring the global topology of the universe - Fagundes, H. V. (Sociedade Brasileira Fisica, 2002)
We review the work done by our group on cosmic topology. It ranges from early attempts to solve a famous controversy about quasars through the multiplicity of images, to quantum cosmology in this context and an application to QED renormalization.